(untitled) (CAHIERS MAGELLANES-NS, 2024)
Education is a dynamic process that needs to be improved periodically. The lack of innovative teaching methods in academic disciplines makes medical curricula inadequate to make significant progress toward the future. The objective of this review is to describe and evaluate alternative teaching and learning methods that can be complementary or alternative to traditional lectures to encourage active student participation and a smooth flow of information.